Operationalisation of Internal Analysis Using The Vrio Framework: Assessing Resource and Capability Management in A Bandung-Based Coffee Business (Case Study: Kopi Anjis) - Shavina Alifia; Gallang Perdana Dalimunthe (Pusat Riset dan Inovasi Nasional, 2024)
Finding the source of competitive advantage has become an essential area in the research of strategic management. One of the methods commonly used to assess internal strengths is the VRIO framework. However, the framework does not explain how well resources or capabilities are managed within the company. Therefore, the objective of this paper is to operationalise the VRIO framework by creating assessment scales to evaluate the level of organisational support for strategic resources. A case study was conducted at Kopi Anjis, a Bandung-based coffee business, to identify branding-related resources and assess their value, rarity, imitability, and organisational support. The study uses a Likert-based evaluation adapted from previous research to determine which capabilities offer sustained competitive advantage. Results indicate that while Kopi Anjis possesses several valuable and rare resources, weak organisational management hinders its strategic potential.